Caracterização de alvos com imagens do sensor multiespectral aerotransportado EPS-A 31T apoiado por dados de espectroradiometria - Zanini, Adenilson Farias (2008)
The necessity to identify objects in the ground constituted by several types of materials became a challenge to the remote sensing researchers. This situation promoted new researches about sensors development and stimulated the improvement and the creation of new techniques and tools that assist in characterization of the targets. Following this necessity this research was developed with the objective of characterize urban targets in multispectral images, by means multivariated statistical analysis and supported by ground spectroradiometry. It was used the sensor MSS EPS A 31T, the spectroradiometer FieldSpec Pro FR and the softwares R 2.7 and ERDAS 8.7. It was realized a sensing in a continuous strip over the Federal University of Santa Maria RS in three distinct schedules, at 12:00 pm HBV and 04:00 pm HBV in 17/12/2008 and at 09:00 am HBV in 27/12/2007. The MSS sensor was operated from the R-99B, a FAB aircraft, on 31 channels mode, in the spectral interval of 0,42μm and 12,5μm and space resolution of 2,5m. parallel to the flight it was realized the reading of the radiation reflected by the targets on ground using the spectroradiometer, which operate in the continuous interval from 0,35 μm to 2,5 μm. A methodology allied with the photo interpretation is the analytic statistic, therefore with the technological evolution it became to associate the panchromatic aerial photographic with multispectrals images. The data obtained in the research were recorded and treated in their respective interfaces and converted to mains. The MSS 3 digital values were rejected from the research because of treatment incompatibility. Initially it was made the analysis of the main components, identifying the three main components (MSS sensor channels 7, 3 and 30), answering them for 99,947% and 99,948% of the originals variables variability to MSS 1 and MSS 2 respectively. From that was generated a high contrast image among the constituent materials of the proposed targets. The wavelength intervals of the three main components were retaken to mains structuring to the execution of the regression analysis. The main components were linked with the ground spectroradiometry realized readings, in their respective spectral intervals. The regression coefficients found had answered respectively for 76,99% of the MSS1 depended variables variability and 85,40% of the MSS 2. These percentages had expressed a better adjust in the second regression and in a smaller variability of the residual errors. The residual error s median to MSS 1 was - 0,2869 and to MSS 2 was 0,0851. The model validity verification was executed with the application of the variance analysis (ANOVA) that showed in F test the values: MSS 1= 66,91 e MSS 2 = 116,99. As the values of Ftab (F 5%;3;60) is equal 2,76, it is noticed that the values of Fcalc is bigger than Ftab , (Fcalc > Ftab), to both analysis. Through the obtained results it is concluded that the employed methodology is valid to characterize the proposed targets and the model contribute to distinguish among them in the MSS image analysis.